Nanodrugs: optimism for emerging trend of multidrug resistance - Khan AU (Dove Medical Press, 2012)
Asad U KhanMedical Microbiology and Molecular Biology Laboratory, Interdisciplinary Biotechnology Unit, Aligarh Muslim University, Aligarh, IndiaThis is with reference to an article published recently in your journal regarding the antibiotic activity of chitosan-coated silver nanoparticles.1 This is an inspiring move towards control of infection caused by multidrug-resistant bacteria which has become a serious problem for clinicians and physicians worldwide.2 At the moment, carbapenems are being used as the drugs of choice to combat infections. However, the emergence of carbapenem resistance has changed current remedial approaches in the management of serious infections. One of the latest enzymes, NDM-1 (New Delhi metallo-β-lactamase-1), first identified in a Swedish patient of Indian origin in 2008,3 has been key in the development of resistance to almost all antibiotics. Infection caused by NDM-1 producers is widespread on the Indian subcontinent,4 and is now emerging in the US and other countries throughout the world.5View original paper by Jena and colleagues.